2018
DOI: 10.5713/ajas.17.0490
|View full text |Cite
|
Sign up to set email alerts
|

Genetic parameters for marbling and body score in Anglonubian goats using Bayesian inference via threshold and linear models

Abstract: ObjectiveThe aim of this study was to estimate (co) variance components and genetic parameters for categorical carcass traits using Bayesian inference via mixed linear and threshold animal models in Anglonubian goats.MethodsData were obtained from Anglonubian goats reared in the Brazilian Mid-North region. The traits in study were body condition score, marbling in the rib eye, ribeye area, fat thickness of the sternum, hip height, leg perimeter, and body weight. The numerator relationship matrix contained info… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…The estimated heritability of CR (0.012 and 0.021) was lower than that reported for Holstein cows (0.027 to 0.049) in Japan [ 30 ]. Low DIC of the model with BCS indicated that the model was better than the model without BCS [ 31 ]. The statistical significance of BCS for CR comfirms that BCS should be included in the genetic analysis of CR records.…”
Section: Discussionmentioning
confidence: 99%
“…The estimated heritability of CR (0.012 and 0.021) was lower than that reported for Holstein cows (0.027 to 0.049) in Japan [ 30 ]. Low DIC of the model with BCS indicated that the model was better than the model without BCS [ 31 ]. The statistical significance of BCS for CR comfirms that BCS should be included in the genetic analysis of CR records.…”
Section: Discussionmentioning
confidence: 99%
“…p t e d A r t i c l einterpreted such that the pool of genes affecting the reproductive cycle of an individual and their expression in heifers might be different from that in cows[9].For Bayesian analysis with the use of Gibbs samplings, low values of the Geweke criterion and MCE for NRR and SFI in both heifers and cows indicated that the amount of posteriori of heritability estimates was valid for binary traits. The low value of MCE indicates that the chain size for particular Bayesian analyses is confirmed as reaching convergence[21]. For the two traits in both heifers and cows, narrow interval of CI and small value of DIC indicating that the model is reliable for estimating NRR and SFI.DIC is a parameter for comparing models, being based on posterior distribution of the likelihood ratio[22].The low genetic correlation of traits of heifer with traits of cow may be due to several factors.…”
mentioning
confidence: 99%